Ochronotic Chronic Tendoachilles Rupture Management: A Case Series - Jeremy B Dorai; Issac Jebaraj (Journal of Foot and Ankle Surgery (Asia Pacific))
Background: Alkaptonuria is a rare inherited genetic disorder in which there is a deficiency of the enzyme homogentisate 1,2-dioxygenase. The three characteristics of alkaptonuria are homogentisic-aciduria, ochronosis, and ochronotic arthropathy. Alkaptonuria is usually asymptomatic until the third decade. Dark stains due to discoloration of the urine may be seen in early childhood, but the diagnosis could be delayed until ochronosis has developed. Alkaptonuria, although a rare disease, is highly prevalent among the Gypsy (Vagiriyar/Romani) community in South India. The founder splice mutation found in this population is c.87 + 1G>A (ivs2 + 1G>A). Patients and methods: We have seen seven such patients presenting with chronic tendoachilles rupture (CTR): four hailing from nearby Gypsy settlements and three non-Gypsy patients. The prior knowledge of the association of low backache with tendoachilles enthesopathy enabled us to make a clinical diagnosis of alkaptonuria-induced ochronotic arthropathy. The patients were assessed clinically and investigated radiologically for enthesopathy, ochronotic spondyloarthropathy, and gonarthrosis, along with serological and urinary tests specific for alkaptonuria. Results: Of the seven patients with a mean age of 56, four were female and three were male. We employed the Achilles tendon Total Rupture Score (ATRS) system for the five patients available for follow-up. The patients with higher ATRS scores have knee deformities and kyphosis affecting their ambulation significantly. It is now known that spontaneous tendoachilles rupture is common among alkaptonuria patients. To improve their quality of life, it is advisable to treat them surgically earlier. The recent introduction of nitisinone in India at a reasonable cost raises hope for disease control for the next generation. Conclusion: A high index of suspicion is suggested when assessing a middle-aged patient with the three cardinal symptoms. Diagnosis and evaluation can be performed through cost-effective urine screening and ultrasonography alone. Early surgical intervention must be considered to avoid disabilities that affect longevity.